Effect of respiratory muscle training on pulmonary function in preoperative preparation of tobacco smokers Efeito do treinamento dos músculos respiratórios sobre a função pulmonar no preparo pré-operatório de tabagistas - Carrie Chueiri Ramos Galvan (Acta Cirurgica Brasileira, 2007)
PURPOSE: To evaluate the effect of utilization of a specific training program of respiratory muscles on pulmonary function in tobacco smokers. METHODS: Fifty asymptomatic tobacco smokers with age superior to 30 years were studied, at the moments: A0 - initial evaluation followed by protocol of respiratory exercises; A1 - reevaluation after 10 minutes of protocol application; and A2 - final reevaluation after 2 weeks of training utilizing the same protocol 3 times per week. The evaluation was realized through measures of maximum respiratory pressures (PImax and PEmax), respiratory peak flow (IPF and EPF), maximum voluntary ventilation (MVV), forced vital capacity (FVC) and forced expiratory volume at the 1st second (FEV1). RESULTS: There was no improvement from initial to final evaluation in FVC and FEV1. But there were significant increases in the variables IPF, EPF, MVV and PImax at evaluations A1 and A2. The PEmax variable increased only at evaluation A2. CONCLUSION: The application of the protocol of respiratory exercises with and without additional load in tobacco smokers produced immediate improvement in the performance of respiratory muscles, but this gain was more accentuated after 2 weeks of exercise. OBJETIVO: Avaliar o efeito da utilização de um programa de treinamento específico dos músculos respiratórios sobre a função pulmonar em indivíduos tabagistas. MÉTODOS: Foram estudados 50 indivíduos tabagistas assintomáticos com idade superior a 30 anos, nos seguintes momentos: A0 - avaliação inicial seguida do protocolo de exercícios respiratórios; A1 - reavaliação após 10 minutos da aplicação do protocolo; e A2 -reavaliação final após duas semanas de treinamento utilizando o mesmo protocolo três vezes por semana. A avaliação foi realizada através das medidas de pressões respiratórias máximas (PImax. e PEmax.), picos de fluxo respiratórios (PFI e PFE), ventilação voluntária máxima (VVM), capacidade vital Forçada (CVF) e Volume expiratório forçado no primeiro segundo (VEF1). RESULTADOS: Não houve melhora na CVF e VEF1 da avaliação inicial para a final. Houve aumento significativo das variáveis PFI, PFE, VVM e PImax nas avaliações A1 e A2. A variável PEmax. aumentou somente na avaliação A2. CONCLUSÃO: A aplicação de protocolo de exercícios respiratórios com e sem carga adicional em indivíduos tabagistas produziu melhora imediata na performance dos músculos respiratórios, mas esta melhora foi mais acentuada após duas semanas de exercício.